THE QUALITY OF HUMAN RESOURCES OF VILLAGE GOVERNMENT OFFICIALS IN MANAGING VILLAGE FUNDS IN CENTRAL MALUKU REGENCY - Tuasikal, Nasmaun; Normawati, Normawati; Pattimukay, Hengky V. R. (PUBLICUS : JURNAL ADMINISTRASI PUBLIK, 2024)
The study focuses on the quality of human resources used by village government officials in managing village funds in Central Maluku Regency. This research uses a quantitative method with a sample size of 60 people. There are two types of data used: primary data and secondary data. Data collection was carried out through questionnaires, observations, and documentation. Sociometric analysis tools were used to analyze the data. The analysis results show that the quality of human resources of village government officials in managing village funds in Central Maluku Regency has not yet met expectations, thus requiring improvement according to priorities, namely: If training and mentoring are conducted properly, village funds will be better managed. If the formation of village fund management groups is carried out well, effective village fund management will take place. If supervision and control are optimally implemented, adequate village fund management will be achieved. If cooperation between the government and the community is well established, the desired village fund management will be created. If the social and cultural aspects of the community are well considered, they will support village fund management. Village fund management can run well if village government officials carry it out transparently, accountably, and participatively, thus supporting the achievement of quality management as a tangible manifestation of the quality of human resources of village government officials in managing village funds. The results and findings of this research have implications for improving the quality of the human resources of village government officials in managing village funds in Central Maluku Regency.